Infographics as Historical Publication Media in the Distribution of Tetengers and Monuments to the Struggle of the Physical Revolution 1947-1949 in Bantul Regency - Pangestu, Rani Samudra; Saefudin, Arif; Windarti, Yuli (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Infographics as a medium of historical publication has significant potential in conveying complex information in a simpler and easier to understand way. This research analyses the use of infographics as a medium of historical publication in the distribution of tetrarchs and monuments of the 1947-1949 Physical Revolution in Bantul Regency. The purpose of this research is to examine the effectiveness of infographics in presenting historical information in an interesting and easy-to-understand manner for the public, especially the younger generation. Although there are several sources of history books available, the challenge of presenting complex information in an interesting and effective way for the public, especially the younger generation, remains a significant issue. The research method used is qualitative with a historical methodology approach, which includes the stages of heuristics, verification, interpretation, and historiography. The results show that infographics can effectively improve people's understanding of local historical heritage through a more visual and attractive presentation. By developing infographics that map important locations, this research is expected to enrich historical publications and increase public appreciation of historical events that occurred in Bantul.